Literature Review: Factors Affecting Labor Productivity in the Construction Sector - Pradhana, Rakhan; Adden Trianto; Muhammad Hamzah Fansuri (Journal of Civil Engineering and Planning (JCEP), 2025)
Labor productivity in the construction industry plays a crucial role in project success, particularly in terms of efficiency, cost, and completion time. However, the sector faces persistent challenges in improving productivity due to various factors, such as workforce skills, project management, rapid technological changes, and strict safety regulations. This study aims to identify the dominant factors influencing construction labor productivity using a Systematic Literature Review (SLR) approach. By analyzing 100 scholarly articles from indexed international journals, data synthesis was carried out based on the frequency of factor occurrences in the literature. The findings indicate that communication between project management and workers is the most dominant factor, appearing in 82 references. This is followed by work experience (81 references) and supervisor experience (77 references), highlighting how expertise and leadership at project sites significantly influence workforce efficiency. Additionally, these factors are categorized into ten main groups, with Site Operations & Management being the most influential category (11.93%), followed by Motivation (11.81%) and Construction Workforce (11.57%). Other factors, such as design changes, material quality, and weather conditions, also contribute to productivity, albeit with lower frequencies. These findings underscore the importance of effective project management, clear communication, and workforce experience in enhancing productivity at construction. Nevertheless, the results of this study may not fully apply to all types of projects due to differences in location and project conditions. Therefore, further research is needed to explore the impact of other factors, such as technology and regulations, on improving labor productivity in the construction sector.